Inhibition of signaling downstream of beta‐2 adrenoceptor by propranolol in prostate cancer cells. Issue 3 (14th November 2022) - Alaskar, Aljoharah; Abdulraqeb Ali, Amaal; Hassan, Sazzad; Shinwari, Zakia; Alaiya, Ayodele; von Holzen, Urs; Miller, Lance; Kulik, George
Abstract: Background: There is accumulating evidence that propranolol, an antagonist of beta‐1 and beta‐2 adrenoreceptors, extends survival of patients with prostate cancer; yet it is not known whether propranolol inhibits beta‐adrenergic signaling in prostate cancer cells, or systemic effects of propranolol play the leading role in slowing down cancer progression. Recently initiated clinical studies offer a possibility to test whether administration of propranolol inhibits signaling pathways in prostate tumors, however, there is limited information on the dynamics of signaling pathways activated downstream of beta‐2 adrenoreceptors in prostate cancer cells and on the inactivation of these pathways upon propranolol administration. Methods: Western blot analysis was used to test the effects of epinephrine and propranolol on activation of protein kinase (PKA) signaling in mouse prostates and PKA, extracellular signal‐regulated kinase (ERK), and protein kinase B/AKT (AKT) signaling in prostate cancer cell lines. Results: In prostate cancer cell lines epinephrine induced robust phosphorylation of PKA substrates pS133CREB and pS157VASP that was evident 2 min after treatments and lasted for 3−6 h. Epinephrine induced phosphorylation of AKT in PTEN‐positive 22Rv1 cells, whereas changes of constitutive AKT phosphorylation were minimal in PTEN‐negative PC3, C42, and LNCaP cells. A modest short‐term increase of pERK in response to epinephrine was observed in all tested cell lines. Incubation of prostate cancer cells with 10‐fold molar excess of propranolol for 30 min inhibited all downstream pathways activated by epinephrine. Subjecting mice to immobilization stress induced phosphorylation of S133CREB, whereas injection of propranolol at 1.5 mg/kg prevented the stress‐induced phosphorylation. Conclusions: The analysis of pS133CREB and pS157VASP allows measuring activation of PKA signaling downstream of beta‐2 adrenoreceptors. Presented results on the ratio of propranolol/epinephrine and the time needed to inhibit signaling downstream of beta‐2 adrenoreceptors will help to design clinical studies that examine the effects of propranolol on prostate tumors.